2012
DOI: 10.1136/bmj.e4110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding a diagnostic aid to best practice to manage suspicious pigmented lesions in primary care: randomised controlled trial

Abstract: Objectives To assess whether adding a novel computerised diagnostic tool, the MoleMate system (SIAscopy with primary care scoring algorithm), to current best practice results in more appropriate referrals of suspicious pigmented lesions to secondary care, and to assess its impact on clinicians and patients.Design Randomised controlled trial.Setting 15 general practices in eastern England.Participants 1297 adults with pigmented skin lesions not immediately diagnosed as benign.Interventions Patients were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 32 publications
0
83
0
3
Order By: Relevance
“…Due to its more complex nature, this system is more expensive. A randomised controlled trial has already demonstrated its efficacy among general practitioners versus best practice [27]. Nevertheless, when this efficacy has to be translated in effectiveness and valued in terms of QALYs for a CEA, one of the main obstacles is the lack of data with which to assess the evolution of diagnosed melanomas [28].…”
Section: Periodsmentioning
confidence: 99%
“…Due to its more complex nature, this system is more expensive. A randomised controlled trial has already demonstrated its efficacy among general practitioners versus best practice [27]. Nevertheless, when this efficacy has to be translated in effectiveness and valued in terms of QALYs for a CEA, one of the main obstacles is the lack of data with which to assess the evolution of diagnosed melanomas [28].…”
Section: Periodsmentioning
confidence: 99%
“…12 This study reports the first validation of the 7PCL, according to STAndards for the Reporting of Diagnostic accuracy studies (STARD) criteria, 13 from data collected prospectively as part of a randomised controlled trial (RCT) of adding a SIAscopic diagnostic aid to best practice. 14 The diagnostic performance of the individual items was examined and the diagnostic accuracy of the different scoring checklists was compared for 'clinically significant' (that is, warranting urgent referral from general practice for specialist opinion), and melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…14 In both groups the lesions were assessed using clinical history, naked eye examination, and completion of the Original 7PCL items. In the MoleMate group lesions were also assessed using the MoleMate system.…”
Section: Methodsmentioning
confidence: 99%
“…We had recently published a systematic review of the relationship between time-to-diagnosis and cancer outcomes, 2 in addition to several sitespecific systematic reviews of the symptoms of cancer; 3-7 these were supplemented by the 70 systematic reviews underpinning the 2015 NICE guidance for suspected cancer. 8 The bibliographical databases of all of these reviews were used here, supplemented by our large personal databases of cancer-specific references. Specific literature searches were undertaken where required.…”
Section: Competing Interestsmentioning
confidence: 99%
“…promoting earlier presentation of potential cancer symptoms [3][4][5][6][7] ; the use of new technologies in the assessment of pigmented skin lesions 8 ; the use of computerized decision-support tools in the diagnosis of cancer in primary care 9 ; cancer-specific education for general practitioners (GPs) 5,10 ; direct access to low-dose CT for the early detection of lung cancer in primary care 11 ; and lower symptom thresholds for urgent use of chest radiography 12 . Thus far, no trial has included a sufficiently large cohort to address the issue of whether or not expedited cancer diagnosis in primary care is beneficial, in terms of either mortality or morbidity.…”
Section: [H1] Benefits Of Expedited Symptomatic Diagnosis [H2] Typesmentioning
confidence: 99%